Seasonality in Environmental Conditions Drive Variation in Plankton Communities in a Shallow Tropical Lake - Kondowe, Benjamin N.; Masese, Frank O.; Raburu, Phillip O.; Singini, Wales; Sitati, Augustine; Walumona, Riziki Jacques (Frontiers in Water, 2022)
Factors influencing the spatio-temporal dynamics of plankton communities in small tropical lakes are not well understood. This study assessed plankton communities in response to spatial and seasonal (wet vs dry seasons) changes in environmental variables in Lake Kanyaboli, a small satellite lake on the northern shores of Lake Victoria, Kenya. Water quality variables, including pH, conductivity (EC), dissolved oxygen (DO), temperature, Secchi depth (SD), nitrates (NO3-), nitrites (NO2-), ammonium (NH4+), soluble reactive phosphorus (SRP), total nitrogen (TN), total phosphorus (TP), and chlorophyll-a (Chl-a), were monitored monthly at six sites spread throughout the lake for one year. Phytoplankton and zooplankton samples were collected and analyzed for taxon composition and abundance. Two-way ANOVA showed no significant interaction between site and season for all variables, except Chl-a. A t-test showed significant seasonal differences in SD, DO, NH4+, NO3-, NO2- and TN. Thirty phytoplankton genera were identified belonging to Bacillariophyceae, Chlorophyceae, Cryptophyceae, Cyanophyceae, Euglenoidae, Trebouxiophyceae, and Zygnematophyceae, with Chlorophyceae being the most dominant (42.30%). Zooplankton comprised of 15 genera, belonging to Copepoda (55.4%), Rotifera (27.9%), and Cladocera (16.7%). Two-way ANOVA for plankton abundance showed no significant interaction between site and season, but there were significant differences in community composition between the wet and dry seasons. Canonical correspondence analysis identified water clarity (Secchi depth) and concentrations of dissolved fractions of nitrogen and phosphorus as the major water quality variables driving variation in the composition of plankton communities in the lake. This study showed that seasonality was a major driver of changes in plankton community composition between dry and wet seasons through changes in the concentrations of nutrients (NH4+, NO3-, NO2-, TN and TP). Lake Kanyaboli's phytoplankton community indicated a non-equilibrial state, perhaps due to short residence times of water, especially during the wet season, and dense macrophytes fringing the lake that increase nutrient uptake and limit the dominance of select phytoplankton species. This study shows the importance of long-term studies covering dry and wet seasons to understand the dynamics of plankton communities and their drivers in small tropical waterbodies to inform management and conservation.